The twelfth-century Renaissance : a reader - Novikoff, Alex J. (2017)
"The twelfth century was an age of institutional expansion, intellectual creativity, and high adventure, characterized by patron-monarchs like King Henry II and Eleanor of Aquitaine, poets like Marie de France and Chrétien de Troyes, lovers and intellectuals like Abelard and Heloise, and religious thinkers like Bernard of Clairvaux and Hildegard of Bingen. In his thoughtful introduction to this important new collection of primary source documents, Alex J. Novikoff explores the historiographical debate surrounding the application of the term "Renaissance" to the twelfth century. Classic works as well as a number of lesser known readings, some of which are translated here for the first time, are included. The overwhelming majority of the sources date from 1075 to 1225, with a focus on Northwestern Europe"--
Spiritual Renewal and the formation of theology -- Schools, scholars, and the liberal arts -- Polemical confrontations with Jews, Muslims, and heretics -- Establishing a new order : government and law -- Love and its discontents -- Experimentations in liturgical and secular poetry -- Art and architecture : theory and practice -- Historical writing and romance -- Medicine, science, and translation.
Includes bibliographical references (pages 449-452) and index.
Issued also in electronic format.
Keywords: 1100-1199; Civilization, Medieval -- 12th century -- Sources; Middle Ages -- Sources; Civilization, Medieval; Middle Ages; Sources